Pengaruh Sistem Kehadiran Elektronik (Aplikasi Aku Hadir) dan Tambahan Penghasilan Pegawai Negeri Sipil terhadap Kinerja dengan Kepuasan Kerja sebagai Variabel Intervening di Dinas Pekerjaan Umum Kabupaten Karanganyar - Abdul Rosyid Daruqhutni; Faiz Alghifary; Tyo Ara Prasetya; Rizal Aprilianto; Hisbullah Amir Ramadan; Anindita Aulia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the impact of the digital E-Performance Attendance System, also called Aku Hadir Application, and additional income for civil servants on employee performance at the Karanganyar Regency Public Works Agency, with job satisfaction as an intervening variable. In reaction to the government's efforts to improve governance through performance-based payments, this study examines the impact of implementing an ERP-based attendance and appraisal system on worker satisfaction and productivity. By adopting a quantitative explanatory method, data was collected from 50 civil servants with the help of a structured questionnaire and then analyzed by multiple linear regression with the help of SPSS. The results show that the E-Performance system has a positive effect on performance and job satisfaction, where job satisfaction partially mediates the relationship. In contrast, additional income has no significant direct or indirect impact on performance. The results emphasize the important role of open digital performance monitoring and job satisfaction in improving the productivity of civil servants, with important implications for policy makers to better manage government human resources.